1966
DOI: 10.1161/01.cir.33.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Retinal Circulation in Man

Abstract: By photographic techniques measurements have been made in the human retina of vessel size, arteriovenous oxygen difference across the retina, and mean retinal circulation time. By combination of these methods estimates can be made of relative changes in retinal blood flow rate and in the rate of oxygen delivery from the retinal vascular system. Observations are presented on the response of the normal and diseased retinal circulation to a variety of stimuli, particularly changes in blood oxygen and carbon dioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

1971
1971
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(58 citation statements)
references
References 43 publications
2
53
0
1
Order By: Relevance
“…Determination of the vessel diameters is also a sensitive technique for studying the effect of hyperoxia on the retinal vascular bed. Vasoconstriction in the same range as found in the present study has been reported previously (Hickam et al 1959;Deutsch et al 1983;Riva et al 1983;Grunwald et al 1984;Fallon et al 1985;Pakola & Grunwald 1993;Kiss et al 2002). As both flow and volume were reduced, as judged by BFS and vessel diameters, it is perhaps not surprising that we found no change in either MTT IR or AVP.…”
Section: Oxygen Breathingsupporting
confidence: 92%
See 1 more Smart Citation
“…Determination of the vessel diameters is also a sensitive technique for studying the effect of hyperoxia on the retinal vascular bed. Vasoconstriction in the same range as found in the present study has been reported previously (Hickam et al 1959;Deutsch et al 1983;Riva et al 1983;Grunwald et al 1984;Fallon et al 1985;Pakola & Grunwald 1993;Kiss et al 2002). As both flow and volume were reduced, as judged by BFS and vessel diameters, it is perhaps not surprising that we found no change in either MTT IR or AVP.…”
Section: Oxygen Breathingsupporting
confidence: 92%
“…Vasoconstriction has been reported for pure O 2 breathing (Hickam et al 1959;Deutsch et al 1983;Riva et al 1983;Grunwald et al 1984;Fallon et al 1985;Pakola & Grunwald 1993). Pure O 2 breathing reduces blood flow by approximately 60% as estimated from vessel diameter and velocity determined by laser Doppler (Riva et al 1983;Grunwald et al 1984).…”
Section: Introductionmentioning
confidence: 87%
“…However, it is believed that the retinal venous blood pressure, which remains above the intraocular pressure, is less affected by changes of body position. 28 We therefore considered the changes in effective MABP to represent alterations of the retinal perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…22,28 These data suggest that the reactivity of the cerebral arteries can be estimated well from the reactivity of the retinal arteries.…”
mentioning
confidence: 88%
“…In humans, the increased retinal oxygen tension in light should lead to autoregulatory vasoconstriction (14) in the retina and reduced retinal blood flow in vascularized retinas in light as has been observed in the human retina (15,16).…”
Section: Discussionmentioning
confidence: 88%